Understanding the three-dimensional world from two-dimensional immunofluorescent adjacent sections - Sho Fujisawa; Dmitry Yarilin; Ning Fan; Mesruh Turkekul; Ke Xu; Afsar Barlas; Katia Manova-Todorova (Elsevier, 2015)
Visualizing tissue structures in three-dimensions (3D) is crucial to understanding normal and pathological phenomena. However, staining and imaging of thick sections and whole mount samples can be challenging. For decades, researchers have serially sectioned large tissues and painstakingly reconstructed the 3D volume. Advances in automation, from sectioning to alignment, now greatly accelerate the process. In addition, immunofluorescent staining methods allow multiple antigens to be simultaneously detected and analyzed volumetrically. The objective was to incorporate multi-channel immunofluorescent staining and automation in 3D reconstruction of serial sections for volumetric analysis. Paraffin-embedded samples were sectioned manually but were processed, stained, imaged and aligned in an automated fashion. Reconstructed stacks were quantitatively analyzed in 3D. By combining automated immunofluorescent staining and tried-and-true methods of reconstructing adjacent sections, we were able to visualize, in detail, not only the geometric structures of the sample but also the presence and interactions of multiple proteins and molecules of interest within their 3D environment. Advances in technology and software algorithms have significantly expedited the 3D reconstruction of serial sections. Automated, multi-antigen immunofluorescent staining will significantly broaden the range and complexity of scientific questions that can be answered with this methodology.